The role of portfolios in EFL student teachers' professional development: a case study - Koçoğlu, Zeynep Banu. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The purpose of this study was to analyze the impact of portfolio preparation on the professional development of student teachers in terms of reflective thinking, technology competency and attitude towards technology use in education. Five senior students from Boğaziçi University, Faculty of Education, Department of Foreign Language Education participated in this study. Multiple sets of data for thisstudy came from: (a) questionnaires, (b) interviews, and (c) artifacts from pen/paper and electronic portfolios. Collection of data was completed in two consecutive semesters, Fall 2002 and Spring 2003. To answer the 1stmain research question that focused on the impact of preparing portfolios on EFL student teachers̕ professional development, the perspectives of student teachers and their portfolio artifacts were analyzed. In order to find the participants̕ perspectives about portfolios, a contentanalysis of the interview transcripts was conducted by using Miles and Huberman̕s model (1994) to identify conceptual themes. In order to investigate reflective thinking, portfolio artifacts were analyzed by using Hattonand Smith̕s (1995) framework of types of reflection to determine how the participants used different types ofreflection to describe and justify their behaviors. To answer the 2nd main research question, that is whether use of technology in preparing portfolios affects student teachers̕ professional development, both pre-and posttechnology competency level and technology attitude questionnaires were tabulated and analyzed statistically. The student teachers stated that the portfolio allowed them to be reflective and to make connections betweentheory and practice, which helped them think about theirstrengths and weaknesses in becoming a teacher. The student teachers also felt that during the preparation of portfolios they were able to identify ways to improve their teaching practice. Based on the findings, the datasupported Hatton and Smith̕s view of teachers̕ reflective thinking as a hierarchical developmental sequence. The results, overall, showed that the process ofpreparing a portfolio provided a useful approach to enhancing professional development, with a few negative comments regarding the time, positive comments regarding the support and collaboration from the peers, its contribution to their professional development in terms of reflective thinking and self-confidence. In addition, preparing electronic portfolios by using different technological applications also enhanced professional development of student teachers in terms of facilitating technological competence and increasing attitudes positively toward computer use in education.
Keywords: Portfolios in education.; English language -- Study and teaching.; Second language acquisition.